ANALISA FISIS PENGOLAHAN AIR BERSIH DI PERUSAHAAN DAERAH AIR MINUM TIRTA SIAK PEKANBARU - Imam Wijayasastra Sinaga; Riad Syech; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research has been done on physical analysis of clean water treatment at PDAM Tirta Siak Pekanbaru. The methods that used in this research was an experimental in order to analyze water treatment system, water debit which was distributed in the main pipe, and water velocity in the pipe. Raw water used in the water treatment plant uses water from the Siak River using intake. Intake on this water treatment uses two pumps with capacity of 140 liters / sec are used interchangeably to collect water. Raw water treated by coagulation, flocculation, sedimentation, filtration, and disinfection. Incoming raw water to be processed and distributed to the reservoir as the water ready to be distributed to consumers. Reservoir water discharge was obtained for 110 liters / sec or 410.4 m3/sec. Obtained debit water out of the water volume ratio of a specific time range that depends on the size of the pressure in the pipe. Based on the results of the average debit coming out in May 2014 at 9:00 to 10:00, 10:00 to 11:00, 11:00 to 12:00, 12:00 to 13:00, 13:00 to 14:00, 14:00 to 15:00 is 475,142 m3/sec, 443,594 m3/sec, 426,883 m3/sec, 431.755 m3/sec, 430.432 m3/sec, and 425.980 m3/sec, respectively. Water flow rate obtained 0.604 m/s, 0.610 m/s, 0.605 m/s, 0.612 m/s, 0.629 m/s, and 0.673 m/s, respectively.